Systematic Literature Review : Memanfaatkan Aplikasi Photomath Sebagai Media Belajar Untuk Meningkatkan Kemampuan Komputasi Siswa - Fatimah Zahra; Yahfizham Yahfizham (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2024)
There has been little research on literature studies related to using the PhotoMath application as a learning medium to improve students' computing abilities. The aim of this research is to analyze whether the PhotoMath application can improve students' computing abilities. The previous research article was taken in 2020-2024. The research method used is Systematic Literature Review (SLR) with the PRISMA protocol for all research articles indexed in Google Scholar and Garuda. The search strategy was adjusted to the selection criteria and involved several moderator variables, namely publication year, journal index, and research material. The data obtained is presented in a quantitative descriptive manner. The results of this SLR research show that learning media using the PhotoMath application can improve students' computing abilities if the application is not misused.